2015
DOI: 10.1186/s13223-015-0081-1
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of anti-IL-6 therapies for granulocytic airway inflammation in asthma

Abstract: BackgroundDetermining the cellular and molecular phenotypes of inflammation in asthma can identify patient populations that may best benefit from targeted therapies. Although elevated IL-6 and polymorphisms in IL-6 signalling are associated with lung dysfunction in asthma, it remains unknown if elevated IL-6 levels are associated with a specific cellular inflammatory phenotype, and how IL-6 blockade might impact such inflammatory responses.MethodsPatients undergoing exacerbations of asthma were phenotyped acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 22 publications
2
55
0
2
Order By: Relevance
“…Second, the provoked model of asthma that we used might not be the most effective approach to assess the efficacy of therapies that target non‐type 2 inflammatory pathways. Based on historical data, we expected that ~40% of patients tested using this model would develop airway inflammation during the LAR that was rich in both eosinophils and neutrophils, the inflammatory subtype that we and others have suggested is more likely to respond to TCZ treatment. However, at 7 h postchallenge, only one of the 11 patients was found to have mixed‐granulocytic sputum, with an additional two patients having this subtype at 24 h postchallenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the provoked model of asthma that we used might not be the most effective approach to assess the efficacy of therapies that target non‐type 2 inflammatory pathways. Based on historical data, we expected that ~40% of patients tested using this model would develop airway inflammation during the LAR that was rich in both eosinophils and neutrophils, the inflammatory subtype that we and others have suggested is more likely to respond to TCZ treatment. However, at 7 h postchallenge, only one of the 11 patients was found to have mixed‐granulocytic sputum, with an additional two patients having this subtype at 24 h postchallenge.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] In clinical studies, IL-6 levels have been reported to be elevated in asthmatics, both systemically and in the airways. [21][22][23] In turn, high IL-6 levels have been associated with reduced lung function [24][25][26] and more severe disease symptoms. 24,27 Allergen (but not methacholine) challenge has also been shown to increase serum levels of both IL-6 21 and sIL-6R.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in IBD including Crohn's disease and ulcerative colitis, IL-6 has been associated with mucosal inflammation in gastrointestinal tract mediated by various cellular mechanisms such as the regulation of T cell differentiation, activation, and proliferation (Hunter and Jones 2015;Waldner and Neurath 2014). A recent study in asthma patients demonstrated that IL-6 impaired lung function through exacerbation of mixed eosinophilic-neutrophilic bronchitis (Chu et al 2015). In addition, IL-6-dependent activation of signal transducer and activator of transcription 3 (STAT3)…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, it has suggested that IL-6/IL-6R signaling is a potential therapeutic target in those diseases. Indeed, several pre-clinical studies with model animals have demonstrated that systemic application of an antibody against IL-6 or IL-6R could inhibit the development of inflammation and tumor in respiratory and gastrointestinal tracts (Chu et al 2015;Song et al 2014;Yamamoto et al 2000). Therefore, direct delivery of rIL6scFv to the mucosa using NZ-IL6scFv might be a good strategy for the treatment of IBD, asthma, and cancer of the mucosal tissue, among others.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators found that lung IL‐6 levels were higher for mice exposed to house dust mite intranasally than those exposed to saline. House dust mite provoked inflammatory responses in the airway were blunted in IL‐6 knockout mice and wild‐type mice treated with anti‐IL‐6 antibody, with all airway and tissue cell types including neutrophils and eosinophils significantly reduced . Peters et al demonstrated that high plasma IL‐6 levels were associated with metabolic syndrome (hypertension, diabetes, and higher BMI), worse lung function, and higher risk of exacerbations.…”
Section: Management Of Non‐t2 Asthmamentioning
confidence: 99%